2017
DOI: 10.3389/fphys.2017.00337
|View full text |Cite
|
Sign up to set email alerts
|

Intensity- and Duration-Based Options to Regulate Endurance Training

Abstract: The regulation of endurance training is usually based on the prescription of exercise intensity. Exercise duration, another important variable of training load, is rarely prescribed by individual measures and mostly set from experience. As the specific exercise duration for any intensity plays a substantial role regarding the different kind of cellular stressors, degree, and kind of fatigue as well as training effects, concepts integrating the prescription of both intensity and duration within one model are ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
70
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(74 citation statements)
references
References 66 publications
0
70
0
Order By: Relevance
“…A previous study has used the mean PO in a 20-min TT is used for training intensity prescription and regular performance monitoring [23]. The obtained value might not necessarily represent the boundary between the heavy-and the severe-intensity domain [13,18], but this test is more practical than a 60-min TT and does not involve the burden of multiple MLSS assessments. Although this approach does not solve the issue of training-zone systems that do not directly compare [26], 20-min TT performance is reliable [24] and sensitive to training adaptations [22] and cycling ability [6].…”
Section: Variablesmentioning
confidence: 99%
See 2 more Smart Citations
“…A previous study has used the mean PO in a 20-min TT is used for training intensity prescription and regular performance monitoring [23]. The obtained value might not necessarily represent the boundary between the heavy-and the severe-intensity domain [13,18], but this test is more practical than a 60-min TT and does not involve the burden of multiple MLSS assessments. Although this approach does not solve the issue of training-zone systems that do not directly compare [26], 20-min TT performance is reliable [24] and sensitive to training adaptations [22] and cycling ability [6].…”
Section: Variablesmentioning
confidence: 99%
“…The lactate threshold (LT) model distinguishes three exercise-intensity domains in which the boundaries are the aerobic threshold (LT 1 ) and the anaerobic threshold (LT ) [13,18]. In sports science, training intensity prescription is often based upon target intensity zones defined according to this model [13,18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lactate threshold is the exercise intensity at which the concentration of blood lactate begins to significantly increase compared to the values at resting and is closely related with the anaerobic threshold. This is considered an essential parameter when assessing performance of elite and recreational runners [5,6], prescribing training intensities in endurance sports [7,8] and can be useful for athlete internal load monitoring [9]. Furthermore, nowadays it is fully demonstrated that the lactate threshold is more decisive for endurance sports performance than other variables such as the maximum consumption of oxygen or the running economy [10,11,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The lactate threshold (LT) is the exercise intensity at which the concentration of blood lactate begins to exponentially increase compared to the values at resting. This physiological indicator is considered essential for endurance sports performance from (at least) three different perspectives: monitoring training by assessing the physical condition from an endurance performance perspective [1]; prescribing exercise intensity [2]; and performance estimation [1].…”
Section: Introductionmentioning
confidence: 99%